2015
DOI: 10.1161/circulationaha.115.016382
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MicroRNA-126 Contributes to the Failing Right Ventricle in Pulmonary Arterial Hypertension

Abstract: R ight ventricular (RV) function is a major determinant of functional capacity and survival in pulmonary arterial hypertension (PAH) and other types of pulmonary hypertension.1 Although afterload is a prominent determinant for RV systolic function in PAH, there remains significant variability between patients with PAH in the ability of the RV to adapt to pressure overload and pulmonary resistance.2,3 The mechanisms accounting for this variability in RV adaptability to increased pulmonary load and for the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(188 citation statements)
references
References 49 publications
7
178
2
1
Order By: Relevance
“…Similarly, Potus and colleagues [45] discover that miR-126-3p can improve right heart function in patients with pulmonary hypertension through the Ras/extracellular signal-regulated kinase (ERK)/VEGF pathway by targeting Spred1. underlying mechanism might be that miR-126-3p upregulation increases right heart microvessel density.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Potus and colleagues [45] discover that miR-126-3p can improve right heart function in patients with pulmonary hypertension through the Ras/extracellular signal-regulated kinase (ERK)/VEGF pathway by targeting Spred1. underlying mechanism might be that miR-126-3p upregulation increases right heart microvessel density.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that patients with CAD have lower circulating levels of miR-126, likely playing a role in plaque instability. 47 In PAH, miR-126 was also described as an important player of endothelial integrity and its downregulation in patients with PAH led to decreased vascular density in the RV 33 and peripheral muscle. 32 Thus, these epigenetic alterations may also increase the susceptibility of patients with PAH to develop CAD.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is not surprising because PAH is now recognized not to be restricted to the lungs. [31][32][33][34] Therefore, we hypothesize that sustained activation of BRD4 during PAH will progressively contribute to coronary alterations (CAD or MVD) in these vulnerable patients. This may be attributable to detrimental conditions, such as increased inflammation, known to cause DNA damage and activate this epigenetic reader, 15,17,35 that propagate to the coronary arteries and activate the BRD4 axis in the heart.…”
Section: P Ulmonary Arterial Hypertension (Pah) Is a Vascularmentioning
confidence: 99%
“…Administration of miR-126 mimics ameliorates microvascular density, improves RV function and diminishes fibrosis, whereas antagomiR-mediated miR-126 downregulation exacerbates RV failure. 39 Recent research by Halkein et al proposed the 16-kDa N-terminal fragment of the nursing hormone prolactin (16K PRL) as a potential factor initiating and driving peripartum cardiomyopathy (PPCM). Expression of miR-146a is induced in endothelial cells (ECs) by 16K PRL.…”
Section: Heart Failurementioning
confidence: 99%